2022
DOI: 10.1039/d1ra07719h
|View full text |Cite
|
Sign up to set email alerts
|

Thermal plasma gasification of organic waste stream coupled with CO2-sorption enhanced reforming employing different sorbents for enhanced hydrogen production

Abstract: Bioenergy with carbon capture and storage can be an influential technological route to curb climate change to a significant extent by preventing CO2 discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Vecten et al provide insights into the composition of syngas, reporting the following volume percentages: H 2 (45–65%), CO (15–30%), CO 2 (10–20%), CH 4 (5–10%), and LHV (10.5–12 MJ/m 3 ). A more comprehensive review on thermal plasma gasification can be found in the literature. …”
Section: Tar Destruction/removal: Existing Technologiesmentioning
confidence: 99%
“…Vecten et al provide insights into the composition of syngas, reporting the following volume percentages: H 2 (45–65%), CO (15–30%), CO 2 (10–20%), CH 4 (5–10%), and LHV (10.5–12 MJ/m 3 ). A more comprehensive review on thermal plasma gasification can be found in the literature. …”
Section: Tar Destruction/removal: Existing Technologiesmentioning
confidence: 99%
“…Additionally, the production of synthetic fuel from plastic that has undergone plasma treatment is cost-effective compared with producing energy from fossil fuels, resulting in net profit. Thermal plasma treatment occurs at high speeds and temperatures and produces chemical reactions in which all complex chemical elements are broken down into simple substances and converted into synthetic gases that are combustible fuels. …”
Section: Introductionmentioning
confidence: 99%
“…Thermal plasma treatment occurs at high speeds and temperatures and produces chemical reactions in which all complex chemical elements are broken down into simple substances and converted into synthetic gases that are combustible fuels. 31 33 …”
Section: Introductionmentioning
confidence: 99%
“…Within this context, calcium oxide-containing ceramics seem to possess excellent properties as carbon oxides captors within the sorption-enhanced processes, 5–8 although other alkaline and earth-alkaline ceramics have also been analysed, such as MgO and Li 4 SiO 4 . 9–11 All these works have evidenced that SER processes exhibit great potential in decarbonizing hydrogen production.…”
Section: Introductionmentioning
confidence: 99%